2021
DOI: 10.3390/nu13082729
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Zinc and Copper Circulating Levels and Cardiometabolic Risk Factors in Adults: A Study of Qatar Biobank Data

Abstract: Cardiometabolic risk (CMR) factors increase the likelihood of developing cardiovascular diseases (CVD). In Qatar, 24% of the total deaths are attributed to CVDs. Several nutritional disturbances have been linked to high risk of CVD. Many studies have discussed the effects of zinc (Zn) and copper (Cu) on CMR factors; however, evidence has been controversial. This investigated the association between CMR factors and the status of Zn and Cu, in addition to Zn/Cu ratio. A total of 575 Qatari men and women aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 112 publications
2
6
0
Order By: Relevance
“…found a negative association between plasma Zn levels and obesity (54) . Several other studies similarly found a negative association between plasma Zn levels and waist circumference and/or BMI (55–57) , which is consistent with our findings that plasma Zn was negatively associated with general obesity. In our study, the median dietary Zn intake of the total population was 6·74 mg/d, which was lower than the study by Ju et al .…”
Section: Discussionsupporting
confidence: 93%
“…found a negative association between plasma Zn levels and obesity (54) . Several other studies similarly found a negative association between plasma Zn levels and waist circumference and/or BMI (55–57) , which is consistent with our findings that plasma Zn was negatively associated with general obesity. In our study, the median dietary Zn intake of the total population was 6·74 mg/d, which was lower than the study by Ju et al .…”
Section: Discussionsupporting
confidence: 93%
“…However, in this Mediterranean population, no significant associations were found between plasma Zn levels and these parameters. Other authors found no association between diabetes and the levels of Zn or other trace elements [ 148 , 151 ], even an inverse association with glycated hemoglobin has been reported [ 155 ]. Interestingly, despite not detecting statistically significant associations between plasma Zn concentrations and fasting glucose or diabetes risk, we identified a highly significant positive association between urine Zn concentrations and these parameters in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors inversely related low circulating levels of Zn with systemic inflammatory activity [ 80 ], and with dyslipidemia in the presence of hypertension and hypercholesterolemia [ 149 ]. High Cu levels have been linked with hypertriglyceridemia in newborns [ 150 ], cardiovascular risk [ 77 ], and a positive correlation between Cu levels and total cholesterol and HDL-cholesterol has been described [ 151 ]. However, other authors found no correlation between plasma Cu and Zn and lipid parameters [ 125 , 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Metals can get into people's bodies in a variety of ways, such as air inhalation, skin contact, and digestion. 6 Essential elements could assume an imperative part in human physiological activities, including immunity, metabolism, and development. 7 However, insufficient, or excessive essential elements might apply antagonistic impacts on people health.…”
Section: Introductionmentioning
confidence: 99%
“…Genetics, diet, and lifestyle are currently well‐established risk factors for hypertension, 4 while previous researches have suggested that metal exposure may also be the cause of hypertension's etiology 5 . Metals can get into people's bodies in a variety of ways, such as air inhalation, skin contact, and digestion 6 . Essential elements could assume an imperative part in human physiological activities, including immunity, metabolism, and development 7 .…”
Section: Introductionmentioning
confidence: 99%